Perspektif Komunikasi Islam terhadap dui menre' di kelurahan Ballere Kabupatrn Wajo: Perspektif Komunikasi Islam terhadap dui menre' di kelurahan Ballere Kabupatrn Wajo (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2025)
The main problem of this research is the Islamic Communication Perspective on Dui Menre' (spending money) in Ballere Village, Wajo Regency. This main problem is then broken down into several sub-problems or research questions, namely: 1). What is the Communication Process for Determining the Amount of Dui Menre' in Ballere Village, Wajo Regency? 2). What is the Islamic Communication Perspective on Dui Menre' in Ballere Village, Wajo Regency? This research is a qualitative research using a case study approach. Data sources consisted of religious leaders, traditional leaders, and community leaders. Data collection methods included observation, interviews, documentation, and reference tracing. Data analysis was conducted in three stages: data reduction, data presentation, and drawing conclusions. This research examines the communication process in determining the amount of dui menre' (spending money) in Bugis wedding customs in Ballere Village, Wajo Regency. Dui menre' symbolizes the responsibility of the groom. Although not included in the pillars of marriage in Islam, it is still considered important according to tradition. The determination process involves three stages: mammanu'-manu', madduta, and mappaserrekeng, reflecting cultural and Islamic communication values. The amount of the dui menre' is influenced by the prospective bride's social status, ancestry, education, and occupation. Islam does not require dui menre', but prioritizes the principles of deliberation, honesty, and non-burdensomeness. The implications of this research indicate the need for more open communication patterns that take into account the economic conditions of both parties. Furthermore, public understanding of the position of dui menre' in Islam is still limited, as it is often equated with the dowry (sadaq), when in fact only the dowry is required. Religious leaders, KUA counselors, and preachers play a crucial role in conveying Islamic communication principles such as sincerity, simplicity, and justice through da'wah, premarital guidance, and marriage advice. Thus, Islamic communication can bridge the gap between preserving local culture and implementing Islamic law for the common good.